Assessing the future direction of sustainable development in public hospitals: Time-horizon, path and action. Issue 4 (April 2021) - Rodríguez, Rocío; Svensson, Göran; Ferro, Carlos
Highlights: Facing Covid-19 pandemic needs synchronization among hospitals. The public hospitals studied differ in their interconnected elements of time. The hospitals studied differ in their paths (top-down versus bottom-up). The hospitals studied differ in their specific actions (intra-organizational versus inter-organizational). Provides a three-dimensional framework to assess the future direction of sustainable development. Abstract: Purpose: To assess the future direction of sustainable development in public hospitals, focusing on their short- versus long-term time horizons, top-down versus bottom-up paths, and intra-organizational versus inter-organizational actions. Design/Methodology/approach: The selection of significant health care organizations was based on judgmental sampling. This study applied an inductive approach. The interviewees were identified according to their knowledge of the future direction of their organizations' sustainable development. Findings: The sustainable development of the studied public hospitals is aimed at the synchronization of actions with other hospitals in the public healthcare system. The public hospitals studied differ in their interconnected elements of time (short- versus long-time horizons), paths (top-down versus bottom-up) and specific actions (intra-organizational versus inter-organizational). Research limitations/: implications Offers insights into how to assess the direction of sustainable development in public hospitals. We stress the importance of time, path and action in conjunction. Furthermore, this study provides a three-dimensional framework to assess the future direction of sustainable development in organizations as well as in industries. Both the former and latter characteristics are shaped by the elements of time, path and action. Managerial Implications: Provides a three-dimensional framework of criteria to assess the direction of sustainable development in organizations. The assessment criteria may be used by organizations to assess the direction of other organizations in their industry. Industry associations or authorities may look into the status and future direction of sustainable development in industries or sectors as a whole. The assessment criteria provide an opportunity and foundation to benchmark against others in the same industry and insights to face pandemic as Covid-19. Originality/Value: First study to consider a three-dimensional framework based on time, path and action to assess the future direction of sustainable development in an organization.